2003
DOI: 10.1073/pnas.0237386100
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cholera in Bangladeshi villages by simple filtration

Abstract: Based on results of ecological studies demonstrating that Vibrio cholerae, the etiological agent of epidemic cholera, is commensal to zooplankton, notably copepods, a simple filtration procedure was developed whereby zooplankton, most phytoplankton, and particulates >20 m were removed from water before use. Effective deployment of this filtration procedure, from September 1999 through July 2002 in 65 villages of rural Bangladesh, of which the total population for the entire study comprised Ϸ133,000 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
254
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(264 citation statements)
references
References 23 publications
(21 reference statements)
5
254
0
1
Order By: Relevance
“…Regardless of the mechanisms causing it, the fact that V. cholerae cells derived from cholera stools can have enhanced infectivity has significant epidemiological implications. A recent study in Bangladesh reported that filtering environmental water through four layers of old sari cloth material before consumption reduced the incidence of cholera among villagers by 48% (24). The authors of this study proposed that the reduction in cholera cases occurs because the filtration removes large planktonic material to which V. cholerae is likely attached (24).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Regardless of the mechanisms causing it, the fact that V. cholerae cells derived from cholera stools can have enhanced infectivity has significant epidemiological implications. A recent study in Bangladesh reported that filtering environmental water through four layers of old sari cloth material before consumption reduced the incidence of cholera among villagers by 48% (24). The authors of this study proposed that the reduction in cholera cases occurs because the filtration removes large planktonic material to which V. cholerae is likely attached (24).…”
Section: Discussionmentioning
confidence: 95%
“…A recent study in Bangladesh reported that filtering environmental water through four layers of old sari cloth material before consumption reduced the incidence of cholera among villagers by 48% (24). The authors of this study proposed that the reduction in cholera cases occurs because the filtration removes large planktonic material to which V. cholerae is likely attached (24). We assume that a similar reduction in the incidence of cholera would be observed if V. cholerae in the environment exist as CVEC, which are large clumps of cells possibly derived from human stools, because in theory such clumps can also be eliminated by sari cloth filtration.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most prominent bacterial genera causing disease in aquaculture is Vibrio including Vibrio anguillarum, V. harveyi, V. vulnificus and V. splendidus (Thompson et al ., 2004; Toranzo et al ., 2005). Live feed used in aquaculture is a potential point of entry and vector for pathogenic bacteria (Olafsen, 2001), and several Vibrio species, including the human and fish pathogens V. cholerae, V. vulnificus and V. splendidus, are found in association with zooplankton, for example copepods, which in the marine environment seem to serve as natural Vibrio reservoirs (Sochard et al ., 1979; Heidelberg et al ., 2002; Colwell et al ., 2003; Vezzulli et al ., 2015). The role of copepods as hosts for V. cholerae has especially been studied extensively, and V. cholerae has repeatedly been isolated from the surface, gut and exuviae of these small crustaceans (Huq et al ., 1983; Tamplin et al ., 1990; Gugliandolo et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of this epidemiological association identified V. cholerae attached to plankton in the environment, an observation that was confirmed by microcosm coinfection experiments. The interaction of V. cholerae with zooplankton is particularly intriguing because copepods, a subclass of crustacean zooplankton, have been incriminated in the transmission of this agent from aquatic reservoirs to susceptible human hosts (3).…”
mentioning
confidence: 99%